Development and validation of an LC-MS/MS method for the quantification of tiamulin, trimethoprim, tylosin, sulfadiazine and sulfamethazine in medicated feed. Issue 5 (4th May 2018) - Patyra, Ewelina; Nebot, Carolina; Gavilán, Rosa Elvira; Cepeda, Alberto; Kwiatek, Krzysztof
ABSTRACT: A new multi-compound method for the analysis of veterinary drugs, namely tiamulin, trimethoprim, tylosin, sulfadiazine and sulfamethazine was developed and validated in medicated feeds. After extraction, the samples were centrifuged, diluted in Milli-Q water, filtered and analysed by high performance liquid chromatography coupled to tandem mass spectrometry. The separation of the analytes was performed on a biphenyl column with a gradient of 0.1% formic acid in acetonitrile and 0.1% formic acid in Milli-Q water. Quantitative validation was done in accordance with the guidelines laid down in European Commission Decision 2002/657/EC. Method performances were evaluated by the following parameters: linearity ( R 2   < 0.99), precision (repeatability <14% and within-laboratory reproducibility <24%), recovery (73.58–115.21%), sensitivity, limit of detection (LOD), limit of quantification (LOQ), selectivity and expanded measurement uncertainty ( k.  = 2). The validated method was successfully applied to the 2 medicated feeds obtained from the interlaboratory studies and feed manufactures from Spain in August 2017. In these samples, tiamulin, tylosin and sulfamethazine were detected at the concentration levels declared by the manufacturers. The developed method can therefore be successfully used to routinely control the content and homogeneity of these antibacterial substances in medicated feed. Abbreviations AAFCO – Association of American Feed Control Officials; TYL – tylosin; TIAM – tiamulin fumarate; TRIM – trimethoprim; SDZ – sulfadiazine; SMZ – sulfamethazine; UV – ultraviolet detector; FLD – fluorescence detector; HPLC – high performance liquid chromatography; MS/MS – tandem mass spectrometry; LOD – limit of detection; LOQ – limit of quantification; CV – coefficient of variation; SD – standard deviation; U – uncertainty